2017
DOI: 10.1097/ta.0000000000001663
|View full text |Cite
|
Sign up to set email alerts
|

Relation of antifactor-Xa peak levels and venous thromboembolism after trauma

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
0
21
2
Order By: Relevance
“…Currently, it is not standard practice in ANZ to measure anti-Xa activity in patients receiving prophylactic LMWH. However, existing data suggest dose adjustment based on peak anti-Xa levels, may reduce the incidence of deep vein thrombosis (DVT) [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is not standard practice in ANZ to measure anti-Xa activity in patients receiving prophylactic LMWH. However, existing data suggest dose adjustment based on peak anti-Xa levels, may reduce the incidence of deep vein thrombosis (DVT) [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, higher empirical dosing (e.g. 30 mg SC enoxaparin BD) may still provide inadequate chemoprophylaxis in many patients, as evidenced by low anti-Xa activity and the development of VTE [12][13][14][15]17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Karcutskie et al demonstrated no difference in VTE rates in patients undergoing dose escalation to achieve peak values of 0.2-0.4 IU/mL. 3 Costantini et al demonstrated that dose escalation improved anti-Xa peak levels, but no difference in VTE rate was seen in this small study. Recently, however, improved outcome was observed in postoperative cancer patients.…”
Section: Discussionmentioning
confidence: 57%
“…Much attention has been given to using anti-Xa levels to guide enoxaparin dosing, but these studies have largely concentrated on examination of peak anti-Xa levels and have shown poor correlation between the adequate peak level and VTE rates. 3,12 Effective reduction of VTE rates with this strategy has not been well demonstrated, and a definitive strategy is lacking. Alternatively, adequate anti-Xa trough levels are associated with protection from VTE in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation